Promises and pitfalls for recombinant oligoclonal antibodies-based therapeutics in cancer and infectious disease. (June 2016) - Corti, Davide; Kearns, Jeffrey D
Graphical abstract: Highlights: Heterogeneity and plasticity are key obstacles in cancer and infectious diseases. Oligoclonal antibodies are uniquely suited to address and overcome these obstacles. Numerous oligoclonal mAbs are being developed for cancer and infectious diseases. Development of oligoclonal antibodies present significant, but surmountable challenges. Strategies to overcome these challenges will have broad applicability across disease areas. Abstract : Monoclonal antibodies (mAbs) have revolutionized the diagnosis and treatment of many human diseases and the application of combinations of mAbs has demonstrated improved therapeutic activity in both preclinical and clinical testing. Combinations of antibodies have several advantages such as the capacities to target multiple and mutating antigens in complex pathogens and to engage varied epitopes on multiple disease-related antigens ( e.g . receptors) to overcome heterogeneity and plasticity. Oligoclonal antibodies are an emerging therapeutic format in which a novel antibody combination is developed as a single drug product. Here, we will provide historical context on the use of oligoclonal antibodies in oncology and infectious diseases and will highlight practical considerations related to their preclinical and clinical development programs.